The role of temporal and spectral cues in the temporal integration of pitch and in pitch-based segregation of sound sources - Clark, Nicholas R (2011)
The auditory nerve conveys spectral information, reflecting the location of maximum vibration along the frequency-tuned basilar membrane, and also information reflecting the timing of peaks in the vibrations at each location. Debate continues as to whether pitch is extracted based on the available temporal or spectral representations of tonal stimuli, or both. The aim of the current work was to determine the roles of temporal and spectral harmonicity cues for pitch, under important conditions for understanding speech in multi-talker environments. Two such conditions are the temporal integration of pitch and pitch-based segregation of sound sources.